An Analysis of Litigation Associated with the Use of the Application Form in the Selection Process. - Kethley RB; Terpstra DE (Public Personnel Management)
This study provides empirical data on the actual degree of litigation associated with the use of the application form in the employee selection process. More than 300 federal court cases involving the use of the application form were identified and analyzed. Data is presented that shows the relative frequency of initiation associated with different types of application form questions and inquiries. Data is also provided on the court case outcomes associated with the different types of application form inquiries. Additionally, data is presented that shows that certain job and industry types are at greater risk of litigation than others. The findings of this study can be used by organizations that are interested in reducing their risk of exposure to future initiation. Some general recommendations are offered for developing application forms that are both effective and legally sound.